4- Post-apartheid Politics of Integration at a Residential Student Community in South Africa: A Case Study on Campus - Moguerane, Khumisho (African Sociological Review, 2007)
Student Village is post-graduate residence at a historically white university in South Africa. Over eleven years into a new epoch of non-racialism in South Africa, some students lived in racially segregated communes. There existed a strong notion in the residence being studied that cultural differences between different races made it difficult to share living spaces. This study tries to explain why and how this occurs. Black participants emulated a black township lifestyle, which they considered as the only genuine black culture. This article sees this construction of black culture as part of black students’ struggle to resist experiences of white, Afrikaner culture and domination at the university.